In vitro safety evaluation of human nasal epithelial cell monolayers exposed to carrageenan sinus wash. Issue 12 (12th October 2017) - Ramezanpour, Mahnaz; Murphy, Jae; Smith, Jason L.P.; Vreugde, Sarah; Psaltis, Alkis James
Abstract : Background: Carrageenans have shown to reduce the viral load in nasal secretions and lower the incidence of secondary infections in children with common cold. Despite the widespread use of carrageenans in topical applications, the effect of carrageenans on the sinonasal epithelial barrier has not been elucidated. We investigate the effect of different carrageenans on the sinonasal epithelial barrier and inflammatory response in vitro. Methods: Iota and Kappa carrageenan delivered in saline irrigation solutions applied to air‐liquid interface (ALI) cultures of primary human nasal epithelial cells from chronic rhinosinusitis patients and controls. Epithelial barrier structure was assessed by measuring the transepithelial electrical resistance (TEER) and immunolocalization of F actin. Ciliary beat frequency (CBF), toxicity, and inflammatory response was studied. Results: Kappa or Iota carrageenan in the different solutions was not toxic, did not have detrimental effects on epithelial barrier structure and CBF. Rather, application of Kappa carrageenan significantly increased TEER and suppressed interleukin 6 (IL‐6) secretion in ALI cultures from CRS patients. Conclusion: Kappa or Iota carrageenan solution was safe and did not negatively affect epithelial barrier function. Kappa carrageenan increased TEER and decreased IL‐6 production in CRS patients, indicating positive effects on epithelial barrier function in vitro.